Madiun Kampung Pesilat: Imaging to develop Pencak Silat extracurricular activities in schools - Bayu Krisna Mukti Wibowo; Bayu Budi Prakoso (Sriwijaya Journal of Sport, 2024)
This study aims to analyse the extracurricular development of Pencak Silat in schools, focusing on the role of the formation of the Madiun Icon of Pesilat Village. This qualitative study was conducted at SMAN 1 Dolopo, Madiun Regency. Interviews were conducted with the principal, vice principal for facilities and infrastructure, curriculum, student affairs, extracurricular coaches, and students actively participating in extracurricular education. Data collection focuses on aspects of coaching, condition of facilities and infrastructure, financial management, student achievements, student interests, and extracurricular achievements. Thematic analysis is carried out through data reduction, data presentation, and concluding. The results showed that the coaching was carried out optimally, the icon of Madiun Kampung Pesilat was responded by schools, extracurricular assistance teachers, and trainers positively which was shown by good cooperation. The condition of facilities and infrastructure is related to financial management, the school strives to carry out optimal procurement and maintenance. The achievements achieved by athletes are recorded from the district level to their participation in international events. Students' interest in participating in extracurricular activities is increasingly supported by efforts to fulfil facilities and infrastructure as well as achievements achieved to generate motivation to develop. Extracurricular indicators are realistically determined from student admission to planned achievements. It is concluded that the icon of Madiun Kampung Pesilat has succeeded in playing its role as a driver for schools, teachers, trainers, and students in developing extracurricular pencak silat for the better.